GENERAL POPULATION DISCRIMINATORY ATTITUDE TOWARDS ADULTS AND CHILDREN WITH HIV/AIDS IN INDONESIA - Danik Iga Prasiska; Sangchul Yoon; Myunken Lee; Heejin Kimm (The Indonesian Journal of Public Health, 2022)
Introduction: HIV continues to be a major global public health issue. While the treatment of people with HIV is still being a challenge, social issues towards people with HIV/AIDS gradually growing. HIV stigma is prevalent worldwide being the barrier to HIV prevention and treatment including in Indonesia. The purpose of this research is to explore the association of social demographic and level knowledge about HIV/AIDS with the discriminatory attitudes towards adults and children with HIV/AIDS in the general population in Indonesia. Methods: The type of research is non-reactive research based on secondary data. Chi-square analysis and logistic regression statistics were performed to test the association. Result: The result reported that socio-demographic statistically had a significant association with the discriminatory attitude. Males (OR 0.993 [95% CI 0.990 – 0.995]) tend to have an inclusive attitude towards adults with HIV/AIDS but children with HIV/AIDS (OR 4.235 [95% 4.003 – 4.480]). People with no education (OR 1.625 [95% CI 1.143 – 2.310]), people with primary education (OR 1.465 [95% CI 1.363 - 1.575]), poorest people (OR 1.471 [95% CI 1.361 – 1.590]), and people with low incomplete knowledge about HIV prevention and transmission (OR 4.083 [95% CI 3.752 – 4.444]) significantly had a non-inclusive attitude towards adults with HIV/AIDS. Conclusion: The result of this research suggested that increasing general public knowledge about HIV prevention and transmission is one of the significant methods in reducing discriminatory attitudes towards adults and children with HIV/AIDS. Keywords: attitude, discriminatory, general, population, stigma